Moderasi Fikih Muamalah di Indonesia: Analisis terhadap Paradigma Fatwa Dewan Syariah Nasional - Amirullah Amirullah; Athoillah Islamy; Hamzah Hamzah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2022)
The development of the Islamic economic system in Indonesia is not always with a positive response in the community. This is often triggered by the community paradigm that is still problematic in responding to the various existing sharia economic fatwas. This normative-philosophical research aims to identify the moderation of the Islamic economic fatwa paradigm formulated by the National Sharia Council (DSN)-Indonesian Ulema Council (MUI). The theory of analysis in this study, namely the moderate fiqh paradigm that was initiated by Muhammad Quraish Shihab. The results of the study show that there is a mode of fiqh moderation in the four foundations of the formulation of the sharia economic fatwa by the DSN-MUI. First, al-Taysîr al-Manhaji. This foundation is in line with the fiqh al-muwazanat paradigm which emphasizes efforts to compare the levels of benefit to be chosen which is better in law formulation. Second,. at-Tafriq baina al-Halal wal Haram. This foundation is parallel to the pattern of the fiqh al-awlawiyat paradigm which considers the priority of the benefits and benefits of the fatwa provisions. Third, I'adah al-Nazhar. This foundation is parallel to the fiqh al-ma'aalat paradigm regarding the importance of reviewing the implications of legal provisions that have been set on the basis of more attainable benefit. Fourth, Tahqiq al-Manath. This foundation is parallel to the fiqh al-maqashid paradigm which emphasizes understanding regarding the purpose of a legal provision. The theoretical implications of this research show that Islamic economic fatwas can always be adaptive and contextual.